Waste cooking oil: New efficient carbon source for natamycin production by Streptomyces gilvosporeus Z8. (July 2022) - Zeng, Xin; Yue, Chaoping; Ding, Zixian; Wang, Lulin; Su, Zhiwei; Zeng, Huawei; Zhang, Biao; Li, Feng; Zhu, Mingzhi
Abstract: A large amount of waste cooking oil puts pressure on environmental protection efforts. This study proposes a new disposal approach, that is to reuse it as the carbon source for natamycin production. Unsaturated fatty acids showed cell cytotoxicity while saturated fatty acids improved natamycin biosynthesis. Therefore, after unsaturated fatty acid removal through hydrogenation, 40 g L −1 microparticles of waste frying oil hydrolysates yielded the maximum natamycin titer (2.1 g L −1 ) with the promotion of cell respiration, energy provision and precursor supply. Similar improvements in natamycin production (2.2- fold higher) were also observed in 5-L and 50-L scale cultivations. Repeated fed-batch culture with immobilized cells further increased natamycin batch production (2.9- fold higher) and reduced the culture time by 21.1%. Finally, this strategy led to 500.0% natamycin yield improvement and 64.1% material cost reduction, which is of enormous significance for industrial natamycin production and environmental protection. Graphical Abstract: ga1 Highlights: Waste cooking oil (WO) was reused to produce natamycin for the first time. Hydrolysates of hydrogenated waste oil (HHWO) promoted natamycin production. HHWO decreased oxidative damage, increased intracellular ATP and acetyl CoA. Repeated fed-batch culture with immobilized cells continuously produced natamycin. New strategy reduced material cost, improved natamycin yield and WO output.